2019
DOI: 10.1038/s41598-019-42482-6
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood lymphocyte subpopulations in patients with bipolar disorder type II

Abstract: We investigated the phenotype of peripheral blood lymphocytes of patients with bipolar disorder type II in different phases of the disease in order to check whether there are specific changes in the immune parameters. Lymphocytes subpopulations were analyzed ex vivo with flow cytometry in patients in euthymic, depression or hypomanic phase of the disease and compared with healthy controls. All BD patients were characterized by lower percentage of CD3 + CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Increased CD14 + levels in serum and cerebrospinal fluid (CSF) have also been associated with schizophrenia and bipolar disorder risk ( Jakobsson et al, 2015 ; Johansson et al, 2017 ). Similarly, for the other immune cell types implicated in the MSEA analysis of miRNA blood-brain correlates, significant aberrations in cell subpopulation levels have been reported for various neurological and psychiatric conditions, both in brain tissue ( Busse et al, 2012 ; Geng and Huang, 2021 ; Troscher et al, 2021 ) and peripheral blood samples ( Schleifer et al, 2002 ; Richartz-Salzburger et al, 2007 ; Miller et al, 2013 ; Cacabelos et al, 2016 ; Rocha et al, 2018 ; Furlan et al, 2019 ; Pietruczuk et al, 2019 ), including major depression, schizophrenia, epilepsy, bipolar disorder and Parkinson’s disease, among others, further suggesting a broad, pathophysiological role for changes in inflammation profiles.…”
Section: Discussionmentioning
confidence: 76%
“…Increased CD14 + levels in serum and cerebrospinal fluid (CSF) have also been associated with schizophrenia and bipolar disorder risk ( Jakobsson et al, 2015 ; Johansson et al, 2017 ). Similarly, for the other immune cell types implicated in the MSEA analysis of miRNA blood-brain correlates, significant aberrations in cell subpopulation levels have been reported for various neurological and psychiatric conditions, both in brain tissue ( Busse et al, 2012 ; Geng and Huang, 2021 ; Troscher et al, 2021 ) and peripheral blood samples ( Schleifer et al, 2002 ; Richartz-Salzburger et al, 2007 ; Miller et al, 2013 ; Cacabelos et al, 2016 ; Rocha et al, 2018 ; Furlan et al, 2019 ; Pietruczuk et al, 2019 ), including major depression, schizophrenia, epilepsy, bipolar disorder and Parkinson’s disease, among others, further suggesting a broad, pathophysiological role for changes in inflammation profiles.…”
Section: Discussionmentioning
confidence: 76%
“…Mays et al investigated whether the number or percentage of B cells reflected depressive states and noticed that depressed patients had significantly higher numbers of CD19 + B cells compared to HCs ( 30 ). A recent study that compared BD patients with HCs on distribution of B lymphocyte subsets yielded a similar result: patients with BD who were in remission and depressive episodes had a higher percentage of CD19 + B cells than HCs ( 31 ). The last but not least, Benschop et al showed that acute psychological stress induces a transient increase in lymphocyte numbers, with NK cell counts being the most prominent ( 32 ); on the contrary, Patas et al discovered that decreased NK cell counts were observed in patients with MDD ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 74%
“…The preservation of lymphocyte subpopulations is one of the key steps when studying different types of hematological and immunological disorders [15, 16]. To this aim, in a select group of 19 subjects, we evaluated the ability of the automatic stratification method to guarantee correct recovery of the most representative lymphoid subsets.…”
Section: Resultsmentioning
confidence: 99%